2014
DOI: 10.17843/rpmesp.2013.303.277
|View full text |Cite
|
Sign up to set email alerts
|

Infecciones de transmisión sexual en mujeres de un establecimiento penitenciario de Lima, Perú

Abstract: Con el objetivo de determinar la prevalencia de infecciones de transmisión sexual (ITS) en mujeres privadas de libertad del Establecimiento Penitenciario Chorrillos I en la ciudad de Lima, Perú, se realizó un estudio de tipo transversal que incluyó mediante un muestreo aleatorio simple a mujeres en edades entre los 18 a 54 años. En ellas se analizaron 180 muestras serológicas y 168 muestras de secreción cérvico vaginal. Los agentes etiológicos más prevalentes obtenidos a través de estas muestras fueron Chlamyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
3
0
7
Order By: Relevance
“…Previous studies had already demonstrated worse social conditions 3,15,20,26 , the elevated prevalence of smoking 6,15,26,27 , alcohol and drug use 15,21,26,27 and mental disturbances 27 in incarcerated women.…”
Section: (16%) Strazza Etmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies had already demonstrated worse social conditions 3,15,20,26 , the elevated prevalence of smoking 6,15,26,27 , alcohol and drug use 15,21,26,27 and mental disturbances 27 in incarcerated women.…”
Section: (16%) Strazza Etmentioning
confidence: 98%
“…Studies carried out in several countries, including Brazil, showed a high prevalence of HIV and syphilis infections in incarcerated men 3,5,10,11,12,13 and women 2,3,6,14,15,16,17,18,19,20,21 , reinforcing the importance of serological diagnosis in prisons for the implementation of available intervention. However, Brazilian studies have been carried out in isolated prison units.…”
Section: Introductionmentioning
confidence: 97%
“…Sexually transmitted infections were studied by Garaycochea et al [14] Vasconcelos et al [15] performed a documentary and retrospective research involving women attended at family health centers in the city of Fortaleza, Ceará, Brazil, and identified in colpocytological examinations vaginal affections suggestives of an inflammatory process were caused by G. vaginalis (25.3%), Candida albicans (10.2%) and T. vaginalis (3.1%), with a higher incidence than we found in the city of Nova Iguaçu. These authors commented that in 66.7% of reports of cervical intraepithelial neoplasia type I/HPV, G. vaginalis was present, suggesting a significant association between Human Papilloma Virus DNA and bacterial vaginosis microbiota.…”
Section: /7mentioning
confidence: 99%
“…Quando questionadas sobre os comportamentos de risco vivenciados, as mulheres entrevistadas citaram a múltipla parceria sexual e o envolvimento com drogas, com ênfase para as práticas sexuais desprotegidas. O uso incomum de preservativo durante as relações sexuais também foi evidenciado em outros estudos 2,11 . Além disso, acrescenta-se que, na população carcerária, o aumento do número de casos de HIV também está relacionado ao uso de drogas e à presença de outras IST/AIDS…”
unclassified